Crystal Phase Distribution and Ferroelectricity in Ultrathin HfO2–ZrO2 Bilayers. Issue 1 (9th January 2020) - McBriarty, Martin E.; Narasimhan, Vijay K.; Weeks, Stephen L.; Pal, Ashish; Fang, Huazhi; Petach, Trevor A.; Mehta, Apurva; Davis, Ryan C.; Barabash, Sergey V.; Littau, Karl A.
Abstract : Nanoscale films of HfO2 and ZrO2 are ferroelectric when certain conditions of composition, interface effects, and processing are met. These conditions affect the fraction of the film composed of a ferroelectric crystal phase, but this phase fraction is difficult to measure for ultrathin films. A new method of interpreting X‐ray absorption spectroscopy, informed by X‐ray diffraction analysis, provides the clearest view yet of the crystal phase distribution in bilayers of 3 nm HfO2 and 3 nm ZrO2 . This analysis helps to identify the mechanisms governing the crystallization of HfO2 –ZrO2 films, aiding the engineering of emerging logic and memory devices. For further details see the Editor's Choice article (article number 1900285 ) by Martin E. McBriarty and co‐workers.